2021
DOI: 10.1093/plcell/koab170
|View full text |Cite
|
Sign up to set email alerts
|

The ARP2/3 complex, acting cooperatively with Class I formins, modulates penetration resistance in Arabidopsis against powdery mildew invasion

Abstract: The actin cytoskeleton regulates an array of diverse cellular activities that support the establishment of plant-microbe interactions and plays a critical role in the execution of plant immunity. However, molecular and cellular mechanisms regulating the assembly and rearrangement of actin filaments at plant-pathogen interaction sites remain largely elusive. Here, using live-cell imaging, we show that one of the earliest cellular responses in Arabidopsis thaliana upon powdery mildew attack is the formation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 98 publications
1
51
0
Order By: Relevance
“…PI3P binding inhibits SCAB1 oligomerization, which further impairs AF destabilization and reorganization during ABA-induced stomatal closure ( Yang et al, 2021 ). Several members of other ABP families, such as Villins and ADFs, as well as the upstream regulator of ARP2/3 complex, the WAVE/SCAR complex ( Xiang et al, 2007 ; Zhao et al, 2010 ; Qin et al, 2021 ), bind to and are regulated by phospholipids. These interactions pose the possibility that phospholipids may regulate stomatal movement via multiple mechanism.…”
Section: Response Of Actin-binding Proteins To Upstream Signals In Gu...mentioning
confidence: 99%
“…PI3P binding inhibits SCAB1 oligomerization, which further impairs AF destabilization and reorganization during ABA-induced stomatal closure ( Yang et al, 2021 ). Several members of other ABP families, such as Villins and ADFs, as well as the upstream regulator of ARP2/3 complex, the WAVE/SCAR complex ( Xiang et al, 2007 ; Zhao et al, 2010 ; Qin et al, 2021 ), bind to and are regulated by phospholipids. These interactions pose the possibility that phospholipids may regulate stomatal movement via multiple mechanism.…”
Section: Response Of Actin-binding Proteins To Upstream Signals In Gu...mentioning
confidence: 99%
“…A key question in this field is why host-cell actin filaments assemble quickly following perception of microbial invaders. One proposed model is that a rearranged actin cytoskeletal network provides tracks for the delivery of defense materials; this is supported by observations of an actin patch as well as actin cables focusing on the penetration site during pathogenic and non-pathogenic fungal and oomycete interactions [ 46 , 50 , 51 , 52 ]. These actin-based structures facilitate the deposition of callose, which fortifies the plant cell wall and helps abrogate pathogen invasion [ 19 , 20 , 53 ].…”
Section: Discussionmentioning
confidence: 97%
“…Using a powerful combination of high spatiotemporal resolution imaging and genetic tools, we and others have demonstrated that turnover of single actin filaments is precisely regulated through nucleation, severing, and availability of actin filament plus ends [ 22 , 25 , 58 , 60 , 61 ]. The accumulation of actin filaments during PTI could be contributed through increased actin nucleation by the Arp2/3 complex or formins [ 52 , 62 ] or through inhibition of filament severing by ADF4 [ 19 ]. Heterodimeric capping protein (CP) limits actin filament assembly by preventing addition of monomers to plus ends and preventing filamentā€“filament annealing [ 24 , 25 ] and has been implicated in multiple signaling pathways [ 20 , 21 , 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cortical cytoplasm of epidermal cells contains a dynamic actin array that is rather disordered and comprises comingled actin filament bundles and individual actin filaments (Staiger et al, 2009; Smertenko et al, 2010). Evidence for actin patches or dense dendritic actin networks is limited to certain cell types, such as guard mother cells (Facette et al, 2015), the apex of trichomes (Yanagisawa et al, 2015), or at focal sites elicited by pathogen attack (Hardham et al, 2007; Qin et al, 2021). Our results revealed that the density of actin filaments in the cortical array, extent of filament bundling, as well as filament nucleation frequency all decreased when either the Arp2/3 complex or formins were inhibited, suggesting that formins were not able to maintain the actin abundance at normal levels when the Arp2/3 complex was genetically- or chemically-inhibited, and the Arp2/3 complex also failed to do so when formins were inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…In growing trichome branches, for example, the Arp2/3 complex generates a tip-localized actin filament array constrained by cortical microtubules that coordinates growth (Yanagisawa et al, 2018; Yanagisawa et al, 2015). During fungal invasion, the Arp2/3 complex localizes to the site of penetration peg attack in epidermal pavement cells and generates a large cortical actin filament patch necessary to suppress invasion (Qin et al, 2021). However, the molecular mechanisms by which the Arp2/3 complex coordinates the organization of cortical actin filament arrays in unstimulated cells or how it generates unique arrays in response to biotic and abiotic stress are poorly understood.…”
Section: Introductionmentioning
confidence: 99%